Topological and functional characterization of the F0I subunit of the membrane moiety of the mitochondrial H+-ATP synthase - Houstĕk, J; Kopecký, J; Zanotti, F; Guerrieri, F; Jirillo, E; Capozza, G; Papa, S (European journal of biochemistry, 1988)
Using isolated polypeptides of the F0 sector of bovine heart mitochondrial H+-ATPase, antisera were developed detecting specifically two components of F0. These two components were identified as F0I and oligomycin-sensitivity-conferring protein (OSCP) respectively. Both F0I and OSCP were digested by mild trypsin treatment of submitochondrial particles depleted of the catalytic part of H+-ATPase (USMP). Proteolysis was largely prevented by binding of F1 to F0. Proteolysis of F0I resulted in the formation of three immunoreactive, membrane-bound fragments of apparently 26 kDa, 25.5 kDa and 18 kDa, respectively, indicating that F0I contains trypsin-accessible Arg or Lys residues located close to the end and the middle part of the protein, respectively, which are in intimate contact with F1. Digestion of USMP with trypsin resulted in depression of passive H+ conduction through F0 which could be ascribed to proteolysis of F0I.
Keywords: srdeční mitochondrie; submitochondriální částice; Molecular Weight; biologický transport; Antigens; Submitochondrial Particles; antigeny; molekulová hmotnost; Cell Membrane; Biological Transport; skot; Proton-Translocating ATPases; Mitochondria, Heart; trypsin; antisérum; Trypsin; zvířata; králíci; Binding Sites; Rabbits; protonové ATPasy; Cattle; Immune Sera; buněčná membrána; vazebná místa; Animals